Velocity profiles of high-calibre ice hockey players: a comparison between fixed and dynamic skating blade holders - Psilander, N.; Arndt, A.; Petré, H. (Footwear Science, 2025)
Detailed skating velocity profiles of high-calibre ice hockey players are lacking, and an increasing number of ice hockey players are using dynamic skating blade holders, but the impact of these skates on performance remains unclear. This study aims to compare velocity profiles between dynamic and fixed blade holders across various skating techniques. Twenty high-calibre skaters from one of the three highest-ranked leagues in Sweden (age 19.7 ± 4.1 years, body mass 77.9 ± 7.6 kg) completed three maximal trials involving linear forward sprints, forward c-cuts, and backward c-cuts on two separate occasions using two different types of blade holders. Split times were recorded at 5 m intervals from 5-40 m and average velocity was calculated for each distance segment. Velocity increased every 5 m up to 40 m, independent of the blade holder type across all techniques. No significant differences in performance were observed for linear forward sprinting or forward c-cuts between the blade holder types. However, backward c-cuts showed a significant improvement in speed with the dynamic holders at several intervals: 0-5 m (2.42 m/s vs. 2.38 m/s, p = 0.048), 15-20 m (5.86 m/s vs. 5.76 m/s, p = 0.009), and 35-40 m (6.84 m/s vs. 6.67 m/s, p = 0.021), resulting in 1-2% faster split times. The results indicate that high-calibre skaters progressively increase their velocity up to 40 m in both forward and backward skating, without reaching maximal velocity. Additionally, dynamic blade holders may offer a performance advantage during backward skating, making them a valuable option for players who frequently utilise this technique in competitive play.